K premeni subjekta v sodobni poeziji - Milčák, Marián (Slavistična revija, 2015)
In an effort to defamiliarize the poetic text, poets in various literatures use a procedure that is a substantial transformation of the conventional lyrical subject "I" to the so-called "hypostatized subject". This new form of the poetic subject is a predominant feature of broader epicizing tendencies that cross borders of national literatures and enrich authorial poetics. However, a poetic text with the hypostatized subject cannot be perceived only as a shift from the conventional lyrical subject that is an end in itself. Most authors use it not only as a mythological but also a social and historical reflection of a human personal subject that was failed by history. It is an attempt at a marked and distinctive artistic rendering of human destiny that is embedded to a lesser (Zbigniew Herbert) or greater (Ted Hughes) degree in a particular historical context.
Keywords: Herbert, Zbigniew, 1924-1998; Jurolek, Rudolf, 1956-; lirski subjekt; literarne študije; Polish literature; poljska književnost; poljska poezija; poljski pesniki; primerjalne študije; Slovak literature; slovaška književnost; slovaška poezija; slovaški pesniki